Additional dorsal interspinous stabilisation has no advantage after decompression of degenerative lumbar spinal stenosis - Josephin Cebulla; Lukas P. Staub; Thomas Barz (Brain and Spine)
Introduction: Interspinous devices are an alternative to instrumented fusion for the treatment of lumbar spinal stenosis (LSS) with radiological instability or deformity. The devices claim to improve clinical symptoms by indirect foraminal decompression with fewer complications and similar functional outcomes compared to conventional fusion techniques, and by avoiding a (further) deterioration of the anatomy of the spine while being less invasive than instrumented fusion. Research question: Do interspinous devices provide a benefit in combination with a decompression of degenerative LSS? Material and methods: In this observational study, 117 patients were treated by decompression surgery alone (n = 37), decompression plus instrumented spinal screw fixation and anterior cage support (n = 41) or decompression plus stabilisation with interspinous devices (n = 39). Pelvic tilt, pelvic incidence, lumbar lordosis, and spondylolisthesis were measured on X-ray scans before surgery, 3 and 12 months postoperative. The Oswestry Disability Index, back and leg pain were also assessed. Generalized Estimating Equation regression models were used to determine the relationship between the outcomes and treatment group over time. Results: After interspinous stabilisation surgery the mean pelvic tilt remained at 22.7°, and the difference between the pelvic incidence and lumbar lordosis (PI-LL) remained at 10.5°. In all three groups, the ODI decreased by 14–18 points (p<0.01), and the pain levels decreased by 2.6–3.2 points (p<0.01). Conclusion: We found no scientific evidence to support the use of interspinous devices. The sagittal profile could not be stabilised by this intervention, and no clinical advantage over decompression surgery alone was evident.